Daughter of the Nile - Hou Hsiao Hsien; Chen Hwa-en; Yang Lin; Kao, Jack; Hsin Shu-Fen (The Masters of Cinema Series, 2017)
Taiwanese auteur Hou Hsiao-hsien followed up his highly acclaimed Coming of Age trilogy of films with "Daughter of the Nile", a rich and poignant drama about a young woman struggling to support her family amidst the violent and neon-soaked milieu of 1980's Taipei. Lin (Lin Hsiao-yang) works as a waitress in a fried chicken restaurant, attends night school and pines after her brother's friend, local gigolo Ah-sang (Fan Yang). Increasingly constrained by the casual brutality of the world around her, Lin finds escape imagining herself as the titular Daughter of the Nile, a character from her favourite manga series. Based on the personal experiences of screenwriter, Chu Tien-wen "Daughter of the Nile" is a profoundly moving observation of marginalised youth. [Cover]